1996
DOI: 10.1115/1.2823351
|View full text |Cite
|
Sign up to set email alerts
|

Application of Objective Rates in Mechanical Modeling of Solids

Abstract: A unified formulation is developed for deformation-related spins, and for objective rates based on them. The approach generalizes the underlying concepts, and allows new rates to be constructed. Mathematical and thermodynamic^ restrictions on these are shown. As a result, it can be demonstrated that the Eulerian strain rate is an objective rate of logarithmic strain, based on a spin easily derivable from the general form. Interrelations between other known spins and objective rates emerge very clearly. Consequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 12 publications
0
30
0
Order By: Relevance
“…From Equations (5), (8) and (9) we know that these formulae are extremely dependent on the eigenvalues of B (or C). For keeping the completeness we record here a closedform solution for these eigenvalues (including the case that the eigenvalues are multiple).…”
Section: The Left and Right Cauchy-green Tensors And Their Spectral Dmentioning
confidence: 98%
See 1 more Smart Citation
“…From Equations (5), (8) and (9) we know that these formulae are extremely dependent on the eigenvalues of B (or C). For keeping the completeness we record here a closedform solution for these eigenvalues (including the case that the eigenvalues are multiple).…”
Section: The Left and Right Cauchy-green Tensors And Their Spectral Dmentioning
confidence: 98%
“…Since Truesdell [1][2][3] developed the hypoelasticity theory, the rate constitutive equations have been widely used in inelastic constitutive theory, see for example Green [4], Dafalias [5], Lee et al [6], Hughes [7] and Reinhardt and Dubey [8]. In many general purpose ÿnite element codes the algorithms based on the rate equations occupy an important position.…”
Section: Introductionmentioning
confidence: 99%
“…We employ the logarithmic spin and the Hencky srain, which assure perfect reversibility and therefore zero dissipation in a closed cycle for elastic-only processes (c.f. [55,76]). We assume that material stability is not an issue in the elastic-only regime (this issue is discussed in reference [23]).…”
Section: Continuum Model 1: J2-plasticitymentioning
confidence: 99%
“…For an Eulerian rate formulation of elastoplasticity, the strain rate tensor can be additively decomposed into its elastic and inelastic parts [4,7,8,10,18]:…”
Section: -Continuum Formulation Of Elastoplasticitymentioning
confidence: 99%
“…Sources of such issues have been associated with hypoelastic model non-integrability as a Cauchy and Green elastic material (see for example references [11,15,16]). To resolve such issues, following the work of Lehmann et al [17], Reinhardt and Dubey [18], and Xiao et al [19], a new objective rate of stress, called the D or logarithmic rate, was introduced. Furthermore, Bruhns et al [10] investigated the integrability conditions of the classical hypoelastic model and showed that the grade zero hypoelastic model is unconditionally integrable as a Cauchy and Green elastic material when the logarithmic (D) rate is used in the model.…”
Section: -Introductionmentioning
confidence: 99%